Dari Beginner Menjadi Master: Capacity Building Dinamika Kelompok Relawan Pendampingan TB RO Di Kabupaten Jember - Ririanty, Mury; Ode, Taufan Asrisyah; Luthviatin, Novia; Nafikadini, Iken (UNEJ e-Proceeding, 2023)
Background: Sekawan's is an association of drug-resistant TB sufferers who have recovered and was founded in 2016. Sekawan's need to have more technique in managing groups when conducting education or when they become facilitators of activities is a technical obstacle for human resources, even though the facilitator's job is to clarify the purpose of the meeting and design a suitable process. Participatory, fun, and engaging, managing the conversation process during meetings and encouraging groups to dare to enter creative areas so that the material obtained by participants is easy to understand, significantly reducing boredom using ice breakers. Method: The general aim of this community service activity is to increase the knowledge and skills of the target audience regarding techniques for managing TB education groups through Ice Breaking. This activity lasted 2 months, from situation analysis to reporting and writing articles. The main target is all 13 Sekawan's administrators. Community service techniques, namely increasing knowledge and skills in managing groups through ice breaking, will be held on Saturday, 13 August 2022, at Seger Nusantara Agro Edupark. Results: The result was that there were ten games taught to Sekawan's, >50% of the targets were able to practice being a facilitator that had been trained and the game module media received a certificate of recognition from Sekawan's because it was used as a daily guide when being a facilitator. Conclusion: This activity has shown the enthusiasm of participants in participating in the activity from start to finish from planning, implementation to monitoring and evaluation and received a good response from various parties including Sekawan's partner, namely Lung Hospital which has become a place for direct practice of educating the facilitators as a result of the activity capacity building.Keywords: TB, facilitator, ice-breaking.